2006
DOI: 10.1017/s0012162206000569
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of autonomy skills in adolescents with myelomeningocele

Abstract: This study describes ages of acquisition (AOA) of typical adolescent autonomy skills in a regional cohort of individuals with myelomeningocele (MM), aged 12 to 18 years, with a mean age of 14 years 11 months (SD 2y 5mo). Prospectively collected data over 10 years were analyzed. Regression analysis, using Generalized Estimation Equation, provided 50th centile and 75th centile AOA for each skill. One hundred and fifty-eight participants (90 males, 68 females) attended 378 annual patient visits. Patient contacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 15 publications
2
57
0
1
Order By: Relevance
“…We found individuals with spinal lesions at or above L2 had lower scores on transfers and basic mobility, sports and physical function, and global function scores on the PODCI as well as health scores on the PedsQL TM than those with L3-5 lesions. These findings are similar to those of some other studies [5,9,14,18]. In general, children scoring in the low 80s or below on the PODCI typically function at a lower level than their normally developing peers [10].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found individuals with spinal lesions at or above L2 had lower scores on transfers and basic mobility, sports and physical function, and global function scores on the PODCI as well as health scores on the PedsQL TM than those with L3-5 lesions. These findings are similar to those of some other studies [5,9,14,18]. In general, children scoring in the low 80s or below on the PODCI typically function at a lower level than their normally developing peers [10].…”
Section: Discussionsupporting
confidence: 90%
“…Many other studies reported a similar association [2,3,11,12,16,28]. Davis et al [9] looked at 158 adolescents and reported 84% of the individuals were shunted. They found the subjects had a 25% to 30% delay in autonomy skills, which was explained by cognitive ability more than the level of lesion [9].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Atualmente, têm-se as primeiras gerações adultas com MMC, gerando uma nova demanda de cuidados para a enfermagem de reabilitação. O enfermeiro de reabilitação desempenha um papel fundamental para que a pessoa com MMC atinja o máximo de seu potencial funcional, considerando os limites decorrentes de sua lesão (5) .…”
Section: Introductionunclassified